HEMATOPOIETIC STEM CELL TRANSPLANTATION (HCT) IN CHILDREN WITH AUTISM SPECTRUM DISORDER: CHALLENGES AND THERAPEUTIC STRATEGIES - ASS Ibanez; CM Lustosa; CMMS Parrode; RV Gouveia; MGAD Matos; VC Ginani; LL Quintino; MF Cardoso; LDS Domingues; A Seber (Hematology, Transfusion and Cell Therapy)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by variable levels of impairment in social behavior and communication that can be seen even in the first months of life. The diagnosis is usually best established between 18-months and 3-years of age. Four children with stablished ASD had already been transplanted by our team but a fifth one was diagnosed by the psychology team at the time of the HCT. Objective: This report is to raise awareness of ASD in children undergoing HCT to improve diagnosis and to offer specific therapeutic interventions. Method: Psychological evaluation and follow up, offered to all children and their families. Result: A 1-year and 9-month-old boy underwent allogeneic HCT for the treatment of Myelodysplastic Syndrome (MDS). Due to difficulty in administering medications and eating (he only accepted liquid food), the psychology team reassessed the patient, suggested the possibility of ASD and referred the patient for evaluation. GVHD prophylaxis was adapted to weekly IV methotrexate. The patient was shown to have communication difficulties, low social interaction, restricted interests, repetitive behaviors, echolalia, and excessive use of screens. Due to weight loss, a nasoenteral tube was reinserted after inpatient discharge, later replaced by gastrostomy (G-Tube). He gradually developed partial acceptance of solid foods, improved social interaction, and acquired control of his urinary sphincter. The patient could later start attending school and made gains in the ASD therapeutic process. The healthcare team has been extremely respectful, avoiding excessive noise, unnecessary touching, always explaining each procedure and giving time to the child to adjust and allow it. Two other patients with ASD have significantly improved socialization after the transplant but, if it is due to the psychological interventions or due to a possible anti-inflammatory effect of the stem cell therapy (Dawson G, et al. A Phase II Randomized Clinical Trial of the Safety and Efficacy of Intravenous Umbilical Cord Blood Infusion for Treatment of Children with Autism Spectrum Disorder. J Pediatr. 2020;222:164-173.e5) remains to be studied. Conclusion: We highlight the importance of preparing professionals to diagnose and manage ASD Care during the HCT process. It remains a major challenge and it is worth emphasizing the importance of expanding knowledge and building tools that can help the HCT process.